Effectiveness and Safety of Acupuncture for the Treatment of Alzheimer's Disease: A Systematic Review and Meta-Analysis - Wang, Yun-Yun; Yu, Shao-Fu; Xue, Hong-Yang; Li, Yang; Zhao, Chen; Jin, Ying-Hui (Frontiers in Aging Neuroscience, 2020)
Background: The effects of acupuncture on Alzheimer's disease (AD) outcomes remain controversial. The aim of this review was to evaluate the effectiveness and safety of acupuncture for the treatment of AD. Methods: PubMed, Embase, Web of Science, the Cochrane Central Register of Controlled Trials, Chinese BioMedical Literature Database, VIP Database for Chinese Technical Periodicals, China National Knowledge Infrastructure, and Wanfang Data were searched to identify relevant randomized controlled trials from inception to January 19, 2019. Data were extracted and evaluated by two authors independently. The data analysis was conducted using R (version 3.6.0) and RStudio (version 1.2.1335) software. Results: Thirty trials involving 2,045 patients were included. Acupuncture plus drug therapy may have been more beneficial for general cognitive function in AD patients than drug therapy alone (short-term treatment: MD, mean difference = 1.94, 95% CI: 1.11, 2.77; p < 0.01; medium-term treatment: MD = 4.41, 95% CI: 1.83, 7.00; p < 0.01). People who received acupuncture plus drug therapy attained higher ADL (Activities of Daily Living) scores than patients who received drug therapy alone for medium-term treatment duration (MD = −2.14; 95% CI: −3.69, −0.59; p < 0.01). However, there is no statistically significant difference in subgroup effect on MMSE (Mini-mental Status Examination) and ADLs (p > 0.05) when comparing acupuncture treatment with drug therapy (such as Donepezil hydrochloride, Nimodipine, or Yizhijiannao), or acupuncture plus drug therapy (such as Donepezil hydrochloride, Dangguishaoyaosan, or Jiannaosan) with drug therapy alone. There was also no significant difference in general cognitive function, ADLs, or incidence of adverse events between acupuncture treatment and drug therapy (p > 0.05). Conclusions: This review indicates that acupuncture plus drug therapy may have a more beneficial effect for AD patients than drug therapy alone on general cognitive function in the short and medium term and on ADLs in the medium term. Acupuncture alone may not have superior effects compared with drug therapy on global cognitive function, ADLs, and incidence of adverse events. Duration of treatment may not modify the effect of acupuncture in comparison with drug therapy. Additional large-scale and high-quality clinical trials are needed.